Guidelines for reporting the quality of clinical case reports in Endodontics: a development protocol. (22nd January 2019) - Nagendrababu, V.; Chong, B. S.; McCabe, P.; Shah, P. K.; Priya, E.; Jayaraman, J.; Pulikkotil, S. J.; Dummer, P. M. H.
Abstract: Case reports are used to communicate interesting, new or rare condition/s, innovative treatment approaches or novel techniques. Apart from informing readers, such information has the potential to contribute towards further scientific studies and the development of newer management modalities. In that context, it is important that case reports are presented accurately and deliver all the necessary and pertinent information to the reader. Reporting guidelines are used to inform authors of the quality standards required to ensure their manuscripts are accurate, complete and transparent. The aim of this project is to develop and disseminate new guidelines – Preferred Reporting Items for Case reports in Endodontics (PRICE). The primary aim is to aid authors when constructing case reports in the field of Endodontics to ensure the highest possible reporting standards are adopted. The project leaders (PD and VN) formed a steering committee comprising six additional members. Subsequently, a five‐phase consensus process will be used. The steering committee will develop the PRICE guidelines (PRICE checklist and flow chart) by identifying relevant items (quality standards) derived from the CAse REport guidelines and Clinical and Laboratory Images in Publications principles, focussing on the content of case reports. Following this, the steering committee will identify a PRICE Delphi Group (PDG) consisting of 30 members including academicians, practitioners, and members of the public. The individual items (components) of the PRICE checklist will be evaluated by the PDG based on a 9‐point Likert scale. Only items scored between 7 and 9 by 70% or more members will be included in the draft checklist. The Delphi process will be continued until a consensus is reached and a final set of items agreed by the PDG members. Following this, a PRICE Face‐to‐Face meeting group (PFMG) will be formed with 20 members to achieve a final consensus. The final consensus‐based checklist and flow chart will be evaluated and approved by selected members of the PDG and PFMG. The approved PRICE guidelines will be published in relevant journals and disseminated via contacts in academic institutions and national endodontic societies, as well as being presented at scientific/clinical meetings.